The Progress of Induced Pluripotent Stem Cells as Models of Parkinson’s Disease - Ji-feng Kang; Bei-sha Tang; Ji-feng Guo (Stem Cells International)
In recent years, induced pluripotent stem cells (iPSCs) were widely used for investigating the mechanisms of Parkinson’s disease (PD). Somatic cells from patients with SNCA (α-synuclein), LRRK2 (leucine-rich repeat kinase 2), PINK1 (PTEN induced putative kinase 1), Parkin mutations, and at-risk individuals carrying GBA (β-glucocerebrosidase) mutations have been successfully induced to iPSCs and subsequently differentiated into dopaminergic (DA) neurons. Importantly, some PD-related cell phenotypes, including α-synuclein aggregation, mitophagy, damaged mitochondrial DNA, and mitochondrial dysfunction, have been described in these iPSCs models, which further investigated the pathogenesis of PD. In 2007, Takahashi et al. and Vodyanik et al. generated iPSCs from human somatic cells for the first time. Since then, patients derived iPSCs were applied for disease modeling, drug discovery and screening, autologous cell replacement therapy, and other biological applications. iPSC research has now become a hot topic in a wide range of fields. This review summarizes the recent progress of PD patients derived iPSC models in pathogenic mechanism investigation and potential clinical applications, especially their promising strategy in pharmacological study and DA neurons transplantation therapy. However, the challenges of iPSC transplantation still exist, and it has a long way to go before it can be used in clinical application.